2010
DOI: 10.1002/jbmr.56
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral morphology in aromatase inhibitor–treated males with idiopathic short stature or constitutional delay of puberty

Abstract: Aromatase inhibitors (AIs), blockers of estrogen biosynthesis, delay bone maturation and therefore are used increasingly to promote growth in children and adolescents with growth disorders. The effects of treatment on skeletal health are largely unknown. Since estrogen deficiency is associated with various detrimental skeletal effects, we evaluated in this cross-sectional posttreatment study vertebral body morphology, dimensions and endplates, and intervertebral disks by the use of magnetic resonance imaging (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 26 publications
2
56
0
3
Order By: Relevance
“…As in our study, growth velocities were similar even though IGF levels were lower during letrozole therapy. After 2 years, PAH increased as a consequence of the slowed bone age progression in the treatment group, but the difference did not persist at later follow-up, when neither the 2 cm difference in height nor 4.1 cm difference in PAH was significant (24).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As in our study, growth velocities were similar even though IGF levels were lower during letrozole therapy. After 2 years, PAH increased as a consequence of the slowed bone age progression in the treatment group, but the difference did not persist at later follow-up, when neither the 2 cm difference in height nor 4.1 cm difference in PAH was significant (24).…”
Section: Discussionmentioning
confidence: 83%
“…They reported no difference in growth velocities over 2 years, but the diminished progression in bone age resulted in a 5.9 cm gain in PAH after 2 years of letrozole compared with no increase from placebo. However, the gain in PAH did not persist in the 22 boys seen in long-term follow-up (24). Salehpour et al (25) treated 91 boys with CDGP and predicted short stature with letrozole, oxandrolone, or placebo for 2 years and reported an increased PAH from baseline (6.1 cm) in the letrozole group only.…”
mentioning
confidence: 96%
“…Despite the neutral findings of the current study, letrozole remains an experimental treatment for growth disorders, particularly due to its possible adverse effects on bone. Letrozole appears to suppress bone turnover and stimulate cortical bone growth in pubertal males (41), and the treatment may predispose boys to vertebral deformities (42).…”
Section: Discussionmentioning
confidence: 99%
“…Trials using high-dose aromatase inhibition reported deleterious effects. Mild vertebral deformities were detected in 45% of the letrozole-treated boys (38). In elderly men treated with anastrozole 1 mg daily for a year, spinal BMD was significantly decreased (39).…”
Section: Potentially Deleterious Effectsmentioning
confidence: 97%